Panduan Perencanaan Karier Berbasis Prinsip Hidup Toma Loa Se Banari Siswa SMA - Sukria Ahsan; IM Hambali; Nur Hidayah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2021)
The purpose of this study was to produce a description of the content and format of a career planning guide based on the life principles of toma loa se banari that is suitable for helping high school students plan their careers. The method used in this research is research and development using stages from Borg and Gall. The instruments used in this study were (1) expert assessment instruments (2) user assessment instruments and (3) career planning scales. The final result of this research is a product which is a career planning handbook based on the life principle of Toma Loa Se Banari that meets the elements of acceptance consisting of aspects of accuracy, usefulness, worthiness and attractiveness. The results of the effectiveness test conducted at SMA N 1 Tidore City showed that this guide was effective in increasing the career planning of high school students. Given the limitations of the research the researcher hopes that the next researcher will test the effectiveness of other schools in the City of Tidore and be able to develop the local wisdom of the City of Tidore to be applied to the Guidance and Counseling service